PENGARUH VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN PEKERJAAN DASAR ELEKTROMEKANIK - Febri Romadhoni; Soeprijanto; Purwanto Gendroyono (Fakultas Teknik Universitas Negeri Jakarta, 2019)
This research aims to know the influence of media video learning against the basic job of learning results in Electromechanical SMK Negeri 7 Bekasi.This research uses quasi experimental methods with a 2 x 2 factorial design. The population of this research is to grade X Automation Engineering industry in SMK Negeri 7 Bekasi consisting of 2 class, in this research because the number of population is not greater than 100 people respondents, then authors takes 100% of the total population in the Industrial Automation engineering students of class X in SMK Negeri 7 Bekasi as many as 60 students or 2 class.Data analysis techniques used in this research is the analysis of Variants (ANOVA) two lanes. Based on the results of the research can be concluded: (1) there is the influence of the media and media learning powerpoint video against the results of student learning in the subjects basic electromechanical work. Judging from the results of the calculation of the Fh = Ftabel > 14.26 = 4.01 (2) there is a difference in student learning outcomes that are learning to use video media learning and media powerpoint between high and low skilled students viewed from the results of the calculation of the Fh = 137.56 > Ftabel = 4.01. (3) there is no influence of the interaction between learning methods learning video media and media powerpoint student learning results on subjects of basic electromechanical work. evidenced by the Fh = 1.16 < Ftabel = 2.76 ABSTRAK Penelitian ini bertujuan untuk : mengetahui pengaruh media video pembelajaran terhadap hasil belajar Pekerjaan Dasar Elektromekanik di SMK Negeri 7 Bekasi. Penelitian ini menggunakan metode quasi eksperimental dengan rancangan factorial 2x2.Populasi penelitian ini adalah siswa kelas X Teknik Otomasi Industri di SMK Negeri 7 Bekasi yang terdiri dari 2 kelas, pada penelitian ini karena jumlah populasinya tidak lebih besar dari 100 orang responden, maka penulis mengambil 100% jumlah populasi yang ada pada siswa jurusan Teknik Otomasi Industri kelas X di SMK Negeri 7 Bekasi sebanyak 60 siswa atau 2 kelas. Teknik analisis data yang digunakan dalam penelitian ini adalah Analisis Varian (ANAVA) dua jalur. Berdasarkan hasil penelitian dapat disimpulkan: (1) Terdapat pengaruh media video pembelajaran dan media powerpoint terhadap hasil belajar siswa pada mata pelajaran pekerjaan dasar elektromekanik. dilihat dari hasil perhitungan Fh = 14,26 > Ftabel = 4,01 (2) Terdapat perbedaan hasil belajar siswa yang diberi pembelajaran menggunakan media video pembelajaran dan media powerpoint antara siswa berkemampuan tinggi dan rendah dilihat dari hasil perhitungan Fh = 137,56 > Ftabel = 4,01. (3) Tidak terdapat pengaruh interaksi antara metode pembelajaran media video pembelajaran dan media powerpoint terhadap hasil belajar siswa pada mata pelajaran pekerjaan dasar elektromekanik. dibuktikan dengan Fh = 1,16 <Ftabel = 2,76.